Doxorubicin induced histomorphometric changes in testes of albino rat - Sah, Surendra Kumar; Khatiwada, Saroj; Chaudhary, Deepak; Jha, Chandra Bhushan; Bhattacharya, Soumya (Nepal Journal of Biotechnology, 2015)
Anticancer drugs like doxorubicin have been found to affect male gonads thereby leading to infertility. This study was conducted to evaluate the effects of doxorubicin over short, mid and long term on testes of male albino rats. Sixty male albino rats aged 6-8 weeks were taken for study. The rats were randomly divided into 3 groups of experimental (each group containing 10 rats) and 3 groups of control (each group containing 10 rats). The experimental groups were given a single dose of doxorubicin i.e. 10 mg/kg body weight intra-peritoneally and sacrificed after 3 different duration for each group (second week, eighth week and sixteenth week). All rats under 3 control groups were given a single intra-peritoneal dose of 2.5 ml/kg body weight normal saline and sacrificed with their respective experimental groups. Significant difference in diameters (p=0.029) and cross-sectional area (p=0.028) of seminiferous tubules was observed between short term experimental and short term control rats. For both between midterm experimental and midterm control group, and between long term experimental and long term control group, a significant difference in right testis weight (p<0.001 for both), left testis weight (p<0.001 for both), volume of testis (p<0.001 and p=0.038), diameter (p<0.001 for both) and area (p<0.001 for both) of seminiferous tubules was observed. As compared to short term experimental group, midterm experimental group and long term experimental group had significantly lower right testis weight (p<0.001 for both), left testis weight (p<0.001 for both), diameter of seminiferous tubule (p<0.001 for both) and cross-sectional area of seminiferous tubule (p<0.001 both). Cross-sections of the seminiferous tubules of all the control groups had normal architecture. However, there was progressive destruction of seminiferous tubules structure across the experimental groups. Doxorubicin has deleterious effect on seminiferous tubules of albino rat testis. Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 10-14